2020
DOI: 10.1177/0020872820949907
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors influencing social workers’ attitudes toward evidence-based practice: A Chinese study

Abstract: Despite the growing emphasis on evidence-based practice (EBP), Chinese social workers’ adoption of EBP has been slow and limited, due partly to the fact that they often hold negative attitudes toward EBP. This study examined factors that account for these negative attitudes, using data collected from social workers in Hong Kong. Regression revealed that females, those less experienced, and social workers in non-governmental organizations endorsed more positive attitudes toward EBP, while those providing youth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…The EBPAS‐15 total score had statistically significant according to the gender of the physicians and it was observed that women got higher scores. In accordance with our study, Aarons et al (2010) found that women had higher EBPAS‐15 total scores 8 and Kim et al (2020, China) found that women had more positive global attitudes toward EBP in a study from social workers in Hong Kong 25 . The Openness score increases as the residency year increases; also, Aarons et al (2006) found that older professionals had higher Openness scores 22 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The EBPAS‐15 total score had statistically significant according to the gender of the physicians and it was observed that women got higher scores. In accordance with our study, Aarons et al (2010) found that women had higher EBPAS‐15 total scores 8 and Kim et al (2020, China) found that women had more positive global attitudes toward EBP in a study from social workers in Hong Kong 25 . The Openness score increases as the residency year increases; also, Aarons et al (2006) found that older professionals had higher Openness scores 22 .…”
Section: Discussionsupporting
confidence: 89%
“…In accordance with our study, Aarons et al (2010) found that women had higher EBPAS-15 total scores 8 and Kim et al (2020, China) found that women had more positive global attitudes toward EBP in a study from social workers in Hong Kong. 25 The Openness score increases as the residency year increases; also, Aarons et al (2006) found that older professionals had higher Openness scores. 22 Openness subscale assesses the extent to which the professional is generally open to trying new interventions and would be willing to try or use more structured or manualised interventions.…”
Section: Discussionmentioning
confidence: 94%
“…Guided by cognitive-behavioral and social learning principles, Workplace Triple P has been shown to be effective in reducing work-family conflicts and enhancing parenting efficacy among working parents ( Hartung and Hahlweg, 2011 ; Haslam et al, 2013 ). Though it has yet to be used in the local context, the demonstrated effectiveness of the original Triple P for Hong Kong parents ( Leung et al, 2003 , 2014 ) suggests that Workplace Triple P is also likely to benefit working parents in Hong Kong ( Kim, 2021 ), where practitioners are ready to offer the evidence-based parenting program ( Kim, 2019a , 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…As a variant of Triple P that specifically targets employed parents, Workplace Triple P has been demonstrated to produce a range of positive outcomes, including enhanced parenting efficacy and reduced individual and work-related stress [ 73 , 77 , 78 ]. Although Workplace Triple P has not been used for parents in Hong Kong, an evidence base supporting the effectiveness of the original Triple P in Hong Kong [ 79 , 80 ] indicates that Workplace Triple P is also likely to be a promising option for working parents in Hong Kong, including those working nonstandard hours, while social service professional in Hong Kong are ready to implement the evidence-based parenting program [ 81 , 82 ]. Given the findings of the study, such parenting programs would be particularly beneficial to low-income fathers working nonstandard hours.…”
Section: Discussionmentioning
confidence: 99%